2012
DOI: 10.1111/j.1467-789x.2012.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic roles for calcium and vitamin D in the regulation of body weight

Abstract: Low intakes of calcium and inadequate vitamin D status often cluster with higher prevalence rates of obesity. Consequently, there has been much interest in the mechanisms by which calcium and vitamin D could regulate body weight and adiposity. This review has focused on randomized controlled trials (RCTs) that have manipulated these nutrients and studied pathways of energy balance. Overall, there is consistent evidence that calcium and vitamin D increase whole body fat oxidation after single and multiple meals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 89 publications
(163 reference statements)
2
74
0
7
Order By: Relevance
“…The results of their study showed, receiving low serum levels of vitamin D3 was associated with a higher prevalence of obesity and increased waist circumference. It was also found that vitamin D3 was effective in weight loss by increasing fat oxidation after meals (10). Likewise, Song et al obtained similar findings of Soares et al However, they reported a different mechanism for weight reduction impact of vitamin D. They concluded a role for vitamin D to regulate of fat cell death and lipid metabolism (11).…”
Section: Introductionsupporting
confidence: 65%
“…The results of their study showed, receiving low serum levels of vitamin D3 was associated with a higher prevalence of obesity and increased waist circumference. It was also found that vitamin D3 was effective in weight loss by increasing fat oxidation after meals (10). Likewise, Song et al obtained similar findings of Soares et al However, they reported a different mechanism for weight reduction impact of vitamin D. They concluded a role for vitamin D to regulate of fat cell death and lipid metabolism (11).…”
Section: Introductionsupporting
confidence: 65%
“…Overall, the data does not consistently support the role of vitamin D (with or without calcium) in weight or FM loss. It also still remains unclear whether vitamin D acts directly by improving insulin sensitivity to facilitate weight loss, or indirectly through increased calcium absorption from the gut and suppression of circulating parathyroid hormone concentrations (66) . A more recent genetic study suggests that VDR target genes may predict individuals who will not respond to supplementation (67) , and inclusion of such individuals in intervention studies may contribute to the equivocal findings presented earlier.…”
Section: Prospective and Intervention Studiesmentioning
confidence: 99%
“…First of all, the use of global knockout models makes it difficult to attribute the observed phenotype to a specific tissue. In addition, these mice were fed a rescue diet containing large amounts of calcium and lactose, and calcium is strongly suspected to regulate energy homeostasis and well known to reduce intestinal lipid absorption (89) . Moreover, in wild-type mice, high-calcium rescue diet (86) has been shown to reduce 1,25(OH) 2 D to extremely low levels similar to Cyp27b1 −/− mice (90) , making it unlikely that the observed effect on body weight is attributable to 1,25(OH) 2 D.…”
Section: Energy Metabolism In Transgenic Mice Models Impacting Vitamimentioning
confidence: 99%